2021
DOI: 10.1111/jfpp.15407
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐induced free radicals production in red wine and model wine by electron paramagnetic resonance spin trapping

Abstract: As an alternative to traditional processing methods, advanced food processing technology such as microwave radiation has been widely used in food industry. Microwave as a new food processing technology used the advantages of microwave energy to overcome the shortcomings of traditional and some new food processing methods. Therefore, microwave irradiation was considered to be a promising technology in food technology such as drying, heating, and sterilizing (Chizoba Ekezie et al., 2017;Guo et al., 2017). In win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
2
6
1
Order By: Relevance
“…In the aging process, free anthocyanins participated in condensation reactions to form new oligomeric and polymeric pigments, thus changing the colour of the wine [ 24 ]; colourless non-anthocyanin phenols (including flavan-3-ols and flavonols) could form yellow pigments through multi-oxidation and decarboxylation reactions [ 25 ], which could also change the colour of the wine. Microwave irradiation could induce the production of free radicals and further initiate chemical reaction in red wine [ 9 ]. These results showed that microwave treatment induced the production of free radicals and triggered chemical reactions to accelerate the production of some stable pigments in red wine.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the aging process, free anthocyanins participated in condensation reactions to form new oligomeric and polymeric pigments, thus changing the colour of the wine [ 24 ]; colourless non-anthocyanin phenols (including flavan-3-ols and flavonols) could form yellow pigments through multi-oxidation and decarboxylation reactions [ 25 ], which could also change the colour of the wine. Microwave irradiation could induce the production of free radicals and further initiate chemical reaction in red wine [ 9 ]. These results showed that microwave treatment induced the production of free radicals and triggered chemical reactions to accelerate the production of some stable pigments in red wine.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the gradual accumulation of coloured pigments in red wine (M 0 , M t3 , and M t6 ), WC increased with the extension of storage time, increasing the visible spectrum at 520 nm [ 1 ]. In addition, the increase of WC in microwave-treated wine was higher, which may be because the microwave-induced free radicals were the most important trigger for chemical reactions related to red wine colouring at 520 nm [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While conventional aging has many benefits, it has the disadvantages of the high cost, cask space, the longer maturation time required, and loss of wine through evaporation. For this concern, alternative techniques have been followed to simplify the process of aging, like the addition of oak chips during bottling (Călugăr et al, 2020; Del Alamo Sanza et al, 2004; Teodosiu et al, 2019), micro‐oxygenation (Canas et al, 2019), ultrasound (Del Fresno et al, 2018; Delgado‐González et al, 2017), microwave (Jing, 2011; Yuan et al, 2021), etc.…”
Section: Introductionmentioning
confidence: 99%